The Influence of Transformational Leadership, Role of Conflict and Job Skill Mismatch on Employee in PT Tambi Wonosobo - Fasya Adil Narinda Islami; Didik Subiyanto; Tri Ratna Purnamarini (Journal of Economy, Accounting and Management Science (JEAMS), 2025)
This study aims to determine the effect of transformational leadership, role of conflict, and job skill mismatch on job satisfaction at PT Tambi in Wonosobo. This study uses quantitative research. In this study, data were collected through questionnaires. The number of employees at PT Tambi Wonosobo is 700 people and the sample taken was 72 people. The results of the study at PT Tambi Wonosobo showed that transformational and job skill mismatch had a positive and subtantial effect, while the role of conflict had a negative and significant effect on job satisfaction. increasing strong business confidence and flexible policies.